Portable Water Cooler using Solar System - Muhamad Hazriq Bin Hamzah; Nor Aira Binti Zambri (Progress in Engineering Application and Technology, 2024)
This project aims to construct a portable solar-powered water cooler. This ingenious system uses a 12V solar panel as the primary energy source and a 12V lead-acid battery for energy storage, which also functions as a backup power supply to assure uninterrupted operation during periods of low sunlight. The cooling method uses a Peltier device coupled to a water block to effectively chill the water. This project entails designing and integrating the solar panel with the battery storage and Peltier cooling system, resulting in effective energy transfer and utilisation. The solar panel charges the lead-acid battery, which then powers the Peltier device to provide the appropriate cooling effect. The experiment shows that the system can provide cooled and clean water, proving the concept of a solar-powered portable water cooler. However, the system did not reach the target temperature established early in the project, highlighting possible areas for additional refinement and development. In conclusion, the study successfully created a practical portable water cooler powered by solar energy, demonstrating the viability of such systems in off-grid situations.